Biological monitoring of heavy metals in blood of Kerman residents, southeast of Iran - Rajabi, Azam; Aghasi, Majid; Roodbari, Ali Akbar (Technium BioChemMed, 2021)
Heavy metals, particularly lead, cadmium, chromium and arsenic, are toxic elements and can cause serious complications for human health. This research is a cross-sectional descriptive study with the aim of biomonitoring heavy metals found in blood of residents in Kerman. Sampling was conducted by random sampling at 8 sites on a total of 80 people (10 per site). The samples were examined by acid digestion using ICP-OES to measure the heavy metals. The results of the present study confirmed a concentration of toxic heavy metals in the blood of residents of Kerman. The maximum concentration of heavy metals were observed in the blood of the residents of Moshtagh and Azadi districts, which were theheavy-traffic areas of the city. A statistically significant relationship was seen between the concentration of some of the above elements and occupation, education and smoking. Statistical tests showed a significant relationship between lead concentration and age. The results suggested that exposure to lead elements can cause some degrees of depression in humans. The presence of toxic heavy metals in the blood of residents can affect their health and also cause some complications.